Observation of the in vivo movement of host keratocytes into donor tissue following corneal graft; a novel technique. Issue 6 (30th November 2009) - Macdonald, E C A; Gregory, M E; Lockington, D; Kennedy, A; Roberts, F; Ramaesh, K
Abstract : Background/aims: The cornea is a highly cellular structure that exists in a dynamic state of cell loss, renewal and replacement. The limbus contains corneal epithelial stem cells. The progenitor or stem cell of the keratocyte remains poorly defined. The authors sought to investigate the in vivo movement of corneal stromal and epithelial cells using a chromosome in situ hybridisation (CISH) technique on human tissue. Methods: Four explanted sex-mismatched human corneal buttons were studied using the CISH technique to identify corneal epithelial and keratocyte cells containing the Y chromosome. Keratocyte identity and lack of infiltrating inflammatory cells were confirmed by immunohistochemistry. The sex mismatch of donor (XX) and host (XY) suggested any identified Y chromosomes cells were of host origin having migrated into the donor tissue. Results: Host corneal epithelial cells were identified in all four buttons, and corneal stromal keratocytes were present in three of the four specimens in the central corneal area. Conclusion: Defining the corneal cell movements and the location of the progenitor or stem cells has important clinical implications. This study has successfully used the CISH technique to demonstrate the in vivo centripetal movement of corneal stromal keratocytes and epithelial cells. The CISH technique may allow further investigation of the corneal stromal dynamics using archival tissue.